Penerapan Pembelajaran Inkuiri Berbantuan Multimedia Untuk Meningkatkan Aktivitas Dan Hasil Belajar Siswa: Studi Pada Mata Pelajaran Kimia Di SMA Negeri 1 Maja - Winarni Yulihandayani (Program Studi Akuntansi IKOPIN, 2022)
The purpose of this study was: (1) To describe the application of multimedia-assisted learning proper inquiry, so as to enhance students' learning activities in the subjects of Chemistry at the State High School Year 1 Maja 2018/2019, (2) To describe the improvement of student learning outcomes application of multimedia-assisted inquiry learning in the subjects of Chemistry at State High School 1 Maja Academic Year 2018/2019, (3) to describe the application of inquiry learning effectiveness of multimedia assisted in improving student learning outcomes when compared with conventional learning in the subjects of Chemistry at State High School 1 Maja Academic Year 2018/2019. Subjects in this study were students of class XI State High School 1 Maja. The research method is a mixture of research methods, namely Classroom Action Research (Classroom Actio Research), the next stage is